👤

rezolvati: x² - 6x=7, prin rezolvarea ecuatiei x² = a

Răspuns :

x²- 6x= 7

x²- 6x- 7= 0

x₁= _6+√6²-4·1·(-7)_                           x₂= _6- √6²- 4·1·(-7)_
               2                                                         2

x₁= _6+√36+ 28_                           x₂= _6- √36+ 28
               2                                                     2

x₁= _6+√64_                                  x₂= _6- √64
            2                                                   2

x₁= _6+8_                                     x₂= _6- 8_
          2                                                   2

x₁= _14_                                       x₂= _-2_
          2                                                   2

x₁= 7                                             x₂= -1